Social representations of depression in the school context - Ribeiro, Karla Carolina Silveira; Oliveira, Josevânia da Silva Cruz de; Coutinho, Maria da Penha de Lima; Araújo, Ludgleydson Fernandes de (Paidéia (Ribeirão Preto), 2007)
This research aimed to apprehend social representations of depression, held by children, in a Basic Public School in João Pessoa, PB, Brazil. A total of 553 children, both genders, aged between 7 and 12 years, participated in the study. The instruments used were: CDI - Children's Depression Inventory, used in the sample screening process, and the projective technique Drawing-story with Theme, analyzed through the model proposed by Coutinho. The data obtained evidence that depression is mainly based on psychosocial factors, reported by children as lack of friends, isolated person, and fear of being rejected. These associations result from children's experiences, as well as information and representations linked to the group they belong to. Concluding, preventive and educational practices, in teaching institutions, with a view to contributing for a better quality of life of these individualsis are needed.